Examining the Relationship between the Synergetic Climate and the Organizational Attractiveness of Schools / Okulların Sinerjik İklimi ile Örgütsel Çekiciliği Arasındaki İlişkinin İncelenmesi - Erdogan, Ufuk; Atik, Servet; Çağırman, Muaz (Erdal TOPRAKCI, 2023)
Schools are organizations that provide education in terms of purpose and scope. Like all other organizations, they have employees and these employees are in a network of relationships. The climatic structure of this network affects the success of the school. The synergetic climate is a key factor that helps maintain organizational continuity and fosters strong interpersonal relationships. One of the most important organizational factors that affects the performance of individuals in their profession and their perceptions and attitudes towards their organization is organizational attractiveness. The main goal of this research is to examine the relationship between the synergetic climate of schools and organizational attractiveness, as perceived by teachers, and to determine if their perceptions of these variables differ based on gender, field of study, years of experience, and working time at the same school. The sample of this study consists of 395 teachers working in Turkey, who were selected using the convenience sampling method. The data was collected using the synergetic climate scale and the organizational attractiveness scale. The results of the study indicate that there is a strong positive correlation between the synergetic climate of schools and organizational attractiveness. Additionally, it was found that the synergetic climate explains 59% of the total variance in the organizational attractiveness.

Okullar amaç ve kapsamı itibariyle eğitim yapılan örgütlerdir. Diğer bütün örgütler gibi çalışanları vardır ve bu çalışanlar bir ilişki ağı içindedir. Bu ağın iklimsel yapısı okulun başarısını etkiler. Sinerjik iklim, örgütün devamlılığını, kişiler arası ilişkilerin güçlü olmasını sağlayan faktörlerden biridir. Bireylerin işlerindeki performansını ve örgütlerine ilişkin algılarını ve tutumlarını etkileyen örgütsel faktörlerden biri ise örgütsel çekiciliktir. Bu araştırmanın temel amacı öğretmenlerin okullarının sinerjik iklimi ile örgütsel çekiciliğine ilişkin görüşleri arasındaki ilişkiyi incelemek, ayrıca bu değişkenlere ilişkin algılarının cinsiyet, branş, kıdem ve okulda çalışma süresinde göre farklılık gösterip göstermediğini belirlemektir. Araştırmanın çalışma grubunu kolayda örnekleme tekniğine göre seçilen Türkiye’deki okullarda görev yapan 395 öğretmen oluşturmaktadır. Araştırmanın verileri sinerjik iklim ölçeği ve örgütsel çekicilik ölçeği ile toplanmıştır. Araştırma sonuçları, öğretmenlerin okullarının sinerjik iklimi ile örgütsel çekicilik düzeyleri arasında yüksek düzeyde pozitif bir ilişki olduğu göstermiştir. Ayrıca sinerjik iklimin, örgütsel çekicilik ölçeğinden alınan puanlara ilişkin toplam varyansın %59’unu açıkladığı belirlenmiştir.
Okulların Sinerjik İklimi ile Örgütsel Çekiciliği Arasındaki İlişkinin İncelenmesi / Examining the Relationship between the Synergetic Climate and the Organizational Attractiveness of Schools
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar